2021
DOI: 10.4049/jimmunol.2100151
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ Manipulates NOD1-Mediated Interaction of Autophagy and Edwardsiella piscicida to Augment Intracellular Clearance in Fish

Abstract: Edwardsiella piscicida is an intracellular pathogenic bacterium accounting for significant losses in farmed fish. Currently, cellular and molecular mechanisms underlying E. piscicida–host cross-talk remain obscure. In this study, we revealed that E. piscicida could increase microtubule-associated protein L chain 3 (LC3) puncta in grass carp (Ctenopharyngodon idella) monocytes/macrophages and a carp cell line, Epithelioma papulosum cyprini. The autophagic response was confirmed by detecting the colocalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Increasing colocalization of A. hydrophila with LC3B puncta in neutrophils was found, and rgcIFN-γ also accelerated the envelopment of bacteria by neutrophil autophagosomes. In fact, previous studies in teleost have reported that rgcIFN-γ promotes monocytes/macrophages autophagy for intracellular E. piscicida clearance [44]. Further involvement of PI3K III and p38 signaling pathways were revealed to mediate rgcIFN-γ-triggered autophagy and drive its bactericidal activity as seen in mammalian macrophages [45].…”
Section: Discussionmentioning
confidence: 94%
“…Increasing colocalization of A. hydrophila with LC3B puncta in neutrophils was found, and rgcIFN-γ also accelerated the envelopment of bacteria by neutrophil autophagosomes. In fact, previous studies in teleost have reported that rgcIFN-γ promotes monocytes/macrophages autophagy for intracellular E. piscicida clearance [44]. Further involvement of PI3K III and p38 signaling pathways were revealed to mediate rgcIFN-γ-triggered autophagy and drive its bactericidal activity as seen in mammalian macrophages [45].…”
Section: Discussionmentioning
confidence: 94%
“…Noteworthily, crosstalk between glutamine and FoxO elucidated that activation of FoxO3 leads to the accumulation of glutamine, which enforced autophagy beneficial for cellular survival; while suppressed FoxO3-mediated autophagy increased apoptosis [ 55 ]. Appropriate apoptosis and autophagy are essential survival strategies for anti-microbial defense, which are highly engaged in fish anti-pathogen responses [ 57 , 66 , 67 ]. Autophagy also favors homeostasis by removing impaired organelles and self-renewal [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, including interferons (IFNs), interleukins (ILs), tumor necrosis factors (TNFs), colony-stimulating factors, and chemokines, could stimulate T and B cells and antigen-presenting cells, mediating the communication between innate and acquired immune in fish. In rainbow trout, higher cytokine abundance in the spleen correlated strongly with lower F. psychrophilum loads in challenged fish ( 28 ). In the present study, the transcript levels of il1β1 , il1β2 , il6 , and il8 continuously increased in the spleen of fish postexposure to F. psychrophilum (at D3 and D7), whereas tnf-α was upregulated at D3 and downregulated slightly at D7 ( Figure 7 , Table S5 ).…”
Section: Discussionmentioning
confidence: 99%